2019
DOI: 10.1002/gcc.22812
|View full text |Cite
|
Sign up to set email alerts
|

A molecular study of synovial chondromatosis

Abstract: Synovial chondromatosis (SC) is a rare benign cartilaginous neoplasm in which recurrent fibronectin 1 (FN1) and activin receptor 2A (ACVR2A) gene rearrangements have been recently reported. Triggered by a case of malignant transformation in SC (synovial chondrosarcoma) showing a novel KMT2A‐BCOR gene fusion by targeted RNA sequencing, we sought to evaluate the molecular abnormalities in a cohort of 27 SC cases using a combined methodology of fluorescence in situ hybridization (FISH) and/or targeted RNA sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 26 publications
0
24
0
1
Order By: Relevance
“…As IDH1/IDH2 mutations seem to be exclusively found in central and periosteal cartilaginous tumours, and are early events in the pathogenesis of these subtypes of cartilaginous tumour, 16,37 we molecularly analysed seven synovial chondrosarcoma cases; however, we did not identify any mutation. To the best of our knowledge, this is the first report of IDH/IDH2 mutations in synovial chondrosarcomas; on the basis of our results, it can be suggested that this molecular marker is not useful in the distinction between synovial chondromatosis and synovial chondrosarcoma.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As IDH1/IDH2 mutations seem to be exclusively found in central and periosteal cartilaginous tumours, and are early events in the pathogenesis of these subtypes of cartilaginous tumour, 16,37 we molecularly analysed seven synovial chondrosarcoma cases; however, we did not identify any mutation. To the best of our knowledge, this is the first report of IDH/IDH2 mutations in synovial chondrosarcomas; on the basis of our results, it can be suggested that this molecular marker is not useful in the distinction between synovial chondromatosis and synovial chondrosarcoma.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly recent studies 38 reported the presence of FN1-ACVR2A and ACVR2A-FN1 in-frame fusions in 31 of 57 (54%) cases of synovial chondromatosis and in two of three secondary synovial chondrosarcomas. 37 These data would indeed support a link between these tumour entities, but unfortunately they cannot help in separating synovial chondromatosis from synovial chondrosarcoma.…”
Section: Discussionmentioning
confidence: 93%
“…Synovial chondromatosis was previously considered to be benign, but it is now classed as having intermediate (locally aggressive) biological potential. Furthermore, recurrent rearrangements of FN1 and/or ACVR2A have been characterised in 57% of cases 52,87,88 . Synovial chondromatosis therefore joins a growing list of mesenchymal tumours with fibronectin gene ( FN1 ) rearrangements outlined earlier that show chondroid matrix production 52,87 .…”
Section: Bonementioning
confidence: 96%
“…52,87,88 Synovial chondromatosis therefore joins a growing list of mesenchymal tumours with fibronectin gene (FN1) rearrangements outlined earlier that show chondroid matrix production. 52,87 It is important to note that FN1/ACVR2A rearrangement may also be detected in chondrosarcomas that can rarely develop from synovial chondromatosis. 88 Chondromyxoid fibroma is now classified as a benign entity (with a local recurrence rate of approximately 10-15%).…”
Section: H O N D R O G E N I Cmentioning
confidence: 97%
See 1 more Smart Citation